The Effect Of Work Stress, Workload, And Work Environment On Turnover Rates At Pt Pesona Lazuardi Agung - Riski Eko Ardianto; Wachid Hasyim; Rika Nurhidayah; Indra Permana (Utan Kayu Publishing, 2025)
High employee turnover remains a strategic challenge for many organizations, including PT Pesona Lazuardi Agung, a company operating in the international trade sector. This study aims to analyze the influence of job stress, workload, and work environment on employee turnover. Adopting a quantitative approach, the research employed the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method, with data collected through structured questionnaires distributed to 44 employees. The findings indicate that all three independent variables positively affect turnover, with workload emerging as the most dominant factor significantly contributing to employees’ intention to leave. Job stress shows a smaller yet significant effect, while the work environment has a moderate impact, particularly when physical conditions and psychosocial relationships are not conducive. This study underscores the importance of managing workload and creating a healthy work environment as essential strategies to improve employee retention. The research is limited by its scope, focusing solely on a single company, and by the use of a quantitative method that does not fully capture the subjective experiences of employees. Future research is recommended to integrate qualitative methods and broaden the organizational scope to gain a more comprehensive and representative understanding of turnover drivers in various industrial contexts.